Interlinking tourism destination competitiveness determinants, travel and tourism competitiveness index and tourism performance / Mohd Hafiz Mohd Hanafiah - Mohd Hanafiah, Mohd Hafiz (2016)
This thesis contributes to the tourism destination competitiveness (TDC) literature by providing validated measures of TDC determinants and empirical understanding of the impact of TDC determinants on the Travel and Tourism Competitiveness Index (TTCI) ranking and tourism performance. The purpose of this thesis was to articulate and test the relationships between TDC determinants, TTCI ranking, and tourism performance by taking into account the effects of the macroeconomic condition of destinations. This study provides an analytic review of TDC determinants with a twofold objective, that is, to test the TDC determinants' statistical soundness and to assess the ability of the determinants in explaining the TTCI ranking and tourism performance complexity. Also, the relationship between TTCI ranking and tourism performance will be examined, and the moderating effect of destination's macroeconomic conditions was tested and analysed. The structural relationship was explored through the examination of underlying TDC theoretical model, as reflected in the literature review. Data from 115 destinations were used to test the hypothesized relationships via partial least square-structural equation modeling (PLS-SEM). Measurement instruments of TDC determinants, TTCI ranking, tourism performance and macroeconomic conditions were adopted and validated based on data collected from secondary sources. The results from the measurement model confirmed the construct of TDC determinants: core resources, complementary resources, infrastructure quality, destination management, environmental management, tourism price and globalisation. Moreover, the structural modeling results provide varying support for the hypotheses defined. First, the results show that the TTCI ranking was merely an index and did not posit causal relationship with the important TDC determinants (tourism core resources and attractions) while four TDC determinants were found to be significant in explaining tourism performance. Second, the TTCI ranking did influence tourism performance positively. However, the Multi-Group Analysis (MGA) result proved that TTCI rankings significantly affect tourism performance in lessdeveloped destinations, but not for the developed ones. This study found that despite the TTCI theoretical importance and usefulness as tools for tourism destinations' ranking, several measurement issues still surround the foundations of TTCI measurements. These findings extend the application of the underpinned theories of TDC studies and contribute to the body of knowledge. Implications of the findings are discussed, and future research directions are recommended.